Development and Statistical Validation of Spectrophotometric Methods for the Estimation of Nabumetone in Tablet Dosage Form - A. R. Rote; S. R. Bhalerao (E-Journal of Chemistry)
Three new simple, economic spectrophotometric methods were developed and validated for the estimation of nabumetone in bulk and tablet dosage form. First method includes determination of nabumetone at absorption maxima 330 nm, second method applied was area under curve for analysis of nabumetone in the wavelength range of 326-334 nm and third method was First order derivative spectra with scaling factor 4. Beer law obeyed in the concentration range of 10-30 μg/mL for all three methods. The correlation coefficients were found to be 0.9997, 0.9998 and 0.9998 by absorption maxima, area under curve and first order derivative spectra. Results of analysis were validated statistically and by performing recovery studies. The mean percent recoveries were found satisfactory for all three methods. The developed methods were also compared statistically using one way ANOVA. The proposed methods have been successfully applied for the estimation of nabumetone in bulk and pharmaceutical tablet dosage form.